Potential of serum sulfatide levels as a marker for classification and disease activity in lupus nephritis - Yamaka, Kosuke; Aomura, Daiki; Harada, Makoto; Nakajima, Takero; Nimura, Takayuki; Hashimoto, Koji; Tanaka, Naoki; Kamijo, Yuji (Frontiers in Immunology, 2025)
IntroductionLupus nephritis (LN) is a severe complication of systemic lupus erythematosus, often leading to end-stage kidney disease. Serum sulfatide levels are linked to severe kidney vasculitis. This study aimed to assess serum sulfatide levels as a marker for classifying and evaluating disease activity in LN.MethodsWe conducted a retrospective study of patients admitted to our hospital between 2003 and 2022. Serum sulfatide levels were compared between LN patients and controls as well as across LN classes based on the International Society of Nephrology/Renal Pathology Society classification. We also analyzed the association between sulfatide levels and active lesions, the Activity Index, and its components.ResultsSerum sulfatide levels were significantly lower in LN patients than in controls (6.90 ± 2.22 vs. 8.34 ± 1.68, P = 0.007). Levels across LN classes were as follows: 9.41 nmol/mL in Class I, 8.21 ± 1.68 nmol/mL in Class II, 7.33 ± 2.25 nmol/mL in Class III, 6.14 ± 1.63 nmol/mL in Class IV, and 7.89 ± 2.12 nmol/mL in Class V, with Class IV having the lowest levels. Serum sulfatides were significantly lower in patients with active lesions (6.38 ± 1.81 vs. 8.23 ± 2.55, P = 0.006) and negatively correlated with the Activity Index (r = −0.51, P < 0.001) and pathological components such as endocapillary hypercellularity, neutrophils/karyorrhexis, and interstitial inflammation (P < 0.001).ConclusionsSerum sulfatide levels were significantly lower in LN patients than in controls and strongly correlated with active lesions and the Activity Index. These findings suggest sulfatide levels as a useful marker for assessing LN disease activity.